2013
DOI: 10.1136/bmjopen-2013-003261
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent intervention to reduce daily sedentary time: a randomised controlled trial

Abstract: ObjectivesTo test the efficacy of a multicomponent technology intervention for reducing daily sedentary time and improving cardiometabolic disease risk among sedentary, overweight university employees.DesignBlinded, randomised controlled trial.SettingA large south-eastern university in the USA.Participants49 middle-aged, primarily female, sedentary and overweight adults working in sedentary jobs enrolled in the study. A total of 40 participants completed the study.InterventionsParticipants were randomised to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
226
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(240 citation statements)
references
References 41 publications
10
226
4
Order By: Relevance
“…One trial reported successful reductions in sitting time by 125 minutes/day over 4 weeks [89], while two longer 12 week randomised controlled trials reduced sitting time 94 minutes/day [90], and 58.7 minutes/day [91] respectively, with reductions in waist circumference compared to a control condition.…”
Section: An Ecological Perspective On Changing Sedentary Behavioursmentioning
confidence: 99%
“…One trial reported successful reductions in sitting time by 125 minutes/day over 4 weeks [89], while two longer 12 week randomised controlled trials reduced sitting time 94 minutes/day [90], and 58.7 minutes/day [91] respectively, with reductions in waist circumference compared to a control condition.…”
Section: An Ecological Perspective On Changing Sedentary Behavioursmentioning
confidence: 99%
“…They included counseling, 45,54,72 appointments with occupational nurses 45 or Registered Dieticians, 71 fitness testing, 45 messages/emails providing feedback on PA, diet, or health promotion, 54,55,62,67,69,71 stages of change-based interventions, 47 personal, partner, or team goal-setting, 44,56,63,64,69 self-monitoring of body mass or PA using activity monitors or questionnaires, 55,56,60,[62][63][64][65]67,68,71 team or individual competitions, 56,64,66 online social networks to connect with friends and make public postings, 64 tailored web-based PA advice, 68 incentives, 56,63,65 PA prescriptions, 43,57 knowledge quizzes, 66 educational materials (eg, leaflets, posters, pamphlets, newsletters, reminders, or fridge magnets), 47,62,66 educational sessions, 57,69 expressions of management support, 66 active workstations, …”
Section: Interventionsmentioning
confidence: 99%
“…When examining individual changes, 87.5 % of participants reduced sedentary time and increased light-intensity physical activity. Several other trials have demonstrated promise in reducing sedentary time among office workers using various interventions that include computer software [26], computer software and text messages [30], sit-stand workstations [23,31], portable pedal bike [24], or an in-person session [32]. Furthermore, the magnitude of changes in sedentary time and light activity in the current trial (sedentary change, −8.1 %; light activity change, 7.9 %) were slightly larger than those seen in a recent trial by Bond et al [33] that used similar technology to interrupt sedentary time (sedentary change, -3.3 to −5.9 %; light activity change, 2.7 to 4.7 %).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have sought to reduce total or leisure sedentary time [22][23][24][25]; however, few have examined breaking up sedentary bouts [26]. Evans et al [26] examined the use of computer software that encourages individuals to stand up every 30 min, but differences in total sedentary time were not observed between the intervention and control groups.…”
Section: Introductionmentioning
confidence: 99%